Experiencia de conservación ex-situ de Solanum fernandezianum (Solanaceae) - SOLANO, JAIME; ANABALÓN, LEONARDO; HAUENSTEIN, ENRIQUE (Gayana Botánica, 2011)
Solanum fernandezianum is an endemic species in danger of extinction the Robinson Crusoe Island, Chile. The fruit was collected during March and April of 2002. The seeds were storaged for a year to 4°C. The percentage of germination in laboratory conditions was 14.3%. After 22 weeks plants initiated fl owering and fruiting. The conservation strategy considered germination of seeds, production of plants in incubation chamber, transplantation to pots and pots arranged in a greenhouse.